Finanční strategie firmy ELMA-THERM, s.r.o. - Koplíková, Iveta (Vysoké učení technické v Brně. Fakulta podnikatelská, 2007)
Diplomová práce hodnotí finanční strategii firmy pomocí ukazatelů finanční analýzy na základě vhodně vybraných metod a jejich interpretace, tj. poznat finanční zdraví, identifikovat slabiny, které by mohli v budoucnu vést k problémům a určit silné stránky, na kterých bych firma mohla stavět. Finanční analýza hodnotí minulost, současnost a předpokládanou budoucnost finančního hospodaření firmy. Obsahuje takové návrhy a opatření, které pomohou eliminovat či maximálně omezit negativní jevy a směřují ke zlepšení finanční situace firmy.

This master’s thesis considers a financial strategy of a company by means of financial indices analysis. On the basis of properly chosen methods and their interpretation the work evaluates a financial health of the company, tries to identify weak points that should be lead up to possible problems in the future and to identify strong points that the company should built on. Financial analysis evaluates past, present and expected future of the company financial economy. It contains proposals and measures that help to eliminate or to maximally reduce negative events and lead up to an improvement of the company financial situation.
The financial strategie of the company ELMA-THERM, s.r.o.
Keywords: strategie; podnik; finanční analýza; vývoj; ukazatel; rentabilita; likvidita; solventnost; aktivita; zadluženost; účetní výkazy; strategy; company; financial analysis; progress; indicator; profitability; solidity; bankability; activity; indebtedness; financial statements